Biotechnology 2.0 - Isea Raúl (Journal of Current Scientific Research, 2023)
Biotechnology has changed our relationships and perspectives of the world, influencing industry and serving as a catalyst for scientific discoveries. With this change, biotechnology enters a new age known as Biotechnology 2.0.
Keywords: Biotechnology 2.0